2009
DOI: 10.1007/s11250-009-9309-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of Oestrus ovis in sheep of Shiraz, southern Iran

Abstract: Two thousand and two heads obtained from slaughtered sheep at the Fars abattoirs (Shiraz, Southern Iran) between April 2006 and April 2007 were examined for the presence of Oestrus ovis larvae. Of the total heads, 995 (49.7%) were infested with O. ovis larvae. O. ovis larvae were observed in both sexes and all age groups in each season of the year. A total of 6264 larvae were collected. The overall larval intensity for the infested sheep was 6.3, with 3.9 in spring, 5.3 in summer, 5.9 in autumn and 7.8 in wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
4
18
3
1
Order By: Relevance
“…This observation is higher than the prevalence of 77.4% in sheep and 72.9% in goats previously reported by Yilma and Genet (2000), 77% in small ruminants recorded in Western Shoa by Tesfaye (1993), and 38.8% prevalence of O. ovis in sheep in Debre Berhan by Bekele and Mukasa-Mugerwa (1994). This variation may be attributed to possible reasons like the differences in agro-ecology like altitude, moisture, and temperatures that determine the fly density, absence of treatments against this parasite, and For similar reasons, the overall and monthly prevalence of O. ovis recorded in both host species in the present study is higher than the prevalence recorded in other parts of the world: 22.6% in sheep and 18.4% in goats in Libiya by Gabaj et al (1993), 58% in sheep (Abo-Shehada et al 2000) and 24% in goats (AboShehada et al 2003) in Jordan, 55.8% in Sicily, Italy by Caracappa et al (2000), 43.4% in sheep and 28.4% in goats in France by Dorchies et al (2000), 71.1% in sheep (Alcaide et al 2003) and 46% in goats (Alcaide et al 2005) in Spain, 59% in sheep in Turkey by Uslu and Dik (2006), 62.07% in sheep in Nigeria by Oniye et al (2006), 49.5% in sheep in Iran by Shoorijech et al (2009), 53% in sheep in Palestine by Othman (2009), and 40.3% in sheep in Turkey by Arslan et al (2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This observation is higher than the prevalence of 77.4% in sheep and 72.9% in goats previously reported by Yilma and Genet (2000), 77% in small ruminants recorded in Western Shoa by Tesfaye (1993), and 38.8% prevalence of O. ovis in sheep in Debre Berhan by Bekele and Mukasa-Mugerwa (1994). This variation may be attributed to possible reasons like the differences in agro-ecology like altitude, moisture, and temperatures that determine the fly density, absence of treatments against this parasite, and For similar reasons, the overall and monthly prevalence of O. ovis recorded in both host species in the present study is higher than the prevalence recorded in other parts of the world: 22.6% in sheep and 18.4% in goats in Libiya by Gabaj et al (1993), 58% in sheep (Abo-Shehada et al 2000) and 24% in goats (AboShehada et al 2003) in Jordan, 55.8% in Sicily, Italy by Caracappa et al (2000), 43.4% in sheep and 28.4% in goats in France by Dorchies et al (2000), 71.1% in sheep (Alcaide et al 2003) and 46% in goats (Alcaide et al 2005) in Spain, 59% in sheep in Turkey by Uslu and Dik (2006), 62.07% in sheep in Nigeria by Oniye et al (2006), 49.5% in sheep in Iran by Shoorijech et al (2009), 53% in sheep in Palestine by Othman (2009), and 40.3% in sheep in Turkey by Arslan et al (2009).…”
Section: Discussionmentioning
confidence: 97%
“…It adversely affects the health and productivity of small ruminants by causing irritation due to rhinitis, sinusitis and pharyngitis, nasal discharge, sneezing, dyspnea, incoordination of movements, circling, emaciation, severe annoyance, and secondary bacterial complications (Murguia et al 2000;Caracappa et al 2000;Tabouret et al 2001;Papadopoulos et al 2001;Alcaide et al 2003;Shoorijech et al 2009). However, Godara et al (2009) have recovered larvae of O. ovis from aberrant sites in mandibular spongy bones of a goat associated with very deep erosions.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between results may be explained in part by the fact that in Bagé, the animals were exposed to O. ovis infestation for a longer period of time (from one month to one year), while in the present experiment the sheep were exposed for just 28 days. Moreover, other factors may have influenced the O. ovis epidemiology, such as the climatic conditions of each region, size of sheep flock and management, which can result in a variable prevalence, as demonstrated by numerous studies conducted in slaughterhouses in different countries (YILMA;DORCHIES, 1991;ABO-SHEHADA et al, 2000;SCALA et al, 2002;ALCAIDE et al, 2003;ARSLAN et al, 2009;SHOORIJEH et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In like manner infection rate in both sexes were also mentioned by different studies (Gebremedhin, 2011;Scholtz et al, 2011;Shoorijeh et al, 2011;Abo-Shehada et al, 2003). While, Radfar and Hajmohammadi (2012) found that female goats were more significantly affected in comparison to male goats.…”
Section: Discussionmentioning
confidence: 77%